Diurnal Pattern of Energy Fluxes Over Rice Field - Mahmud, AA; Baten, MA; Khan, MB; Miyata, A (Journal of Environmental Science and Natural Resources, 2015)
An experiment was conducted to investigate the factors responsible for the partitioning of energy balance components over BRRI dhan 28 (Boro season) rice crop at the paddy field of Bangladesh Agricultural University Farmland, Mymensingh during August 2010 to July 2011. The whole measurement period was divided into two seasons such as Boro rice and Post Boro fellow. Energy balance components were measured in this experiment using sophisticated sensors. The cropping season differences in water and energy fluxes were attributed by the availability of sunlight and abundance of water at the site as well as differences in sunshine hours during winter. Irrigation during winter Boro had substantial influence on the seasonal and inter-annually variability of energy partitioning at rice field. Of the papers diurnal variations in energy balance components are shown and variations in the energy balance components are discussed. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22031 J. Environ. Sci. & Natural Resources, 6(1): 01-06 2013